Tinjauan Parameter Fisik Pantai Mangkang Kulon Untuk Kesesuaian Pariwisata Pantai Di Kota Semarang - Yustishar, Maulana; Pratikto, Ibnu; Koesoemadji, Koesoemadji (977-2407769)
Mangkang Kulon Coast has the potential to be developed to provide benefits to community. This research aimed to overview physic parameter for coastal tourism of Mangkang Kulon Coast, Mangkang Village, Tugu Distric, Semarang Regency. There are 2 beach of sampling, primary sampling on May-June 2009 and field sampling on February-March 2010. Field sampling includes measurements physic parameters and supported by secondary data. This research used descriptive and purposive sampling method. The results showed that the Coast Mangkang Kulon have the potential and suitability as a coastal tourism. The results of measurements in station I, II and III almost similar, it shows of water depth is Â± 2.5 meters (< 5 meter maximum value of depth), slope coast about 3-6Â° so very easy to do tourism activity and oceanography aspect including waves, tides and currents available and support the marine tourism. Although there are several unfavorable parameters such as such turbidity, narrow coast, varies sands size and sand color. However, need strategy to show the better display its advantages such as convenience factor, supporting facilities to cover the shortage. In addition, the presence of mangrove can be an interesting icon visitor's attention so that the government is expected to wisely choose the concept of tourism development on the coast is the most appropriate.